Fetal Alcohol Spectrum Disorders: Survey of Healthcare Providers after Continuing Education - Evans, Shirley F.; Tenkku, Leigh E.; Kennedy, Tay; Zoorob, Roger; Rudeen, P. Kevin (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Fetal alcohol spectrum disorders (FASD) occur as a result of prenatal alcohol exposure and are commonly associated with intellectual disability. Maternal alcohol consumption affects fetal development resulting in numerous lifelong physical, mental, and neurobehavioral abnormalities. To promote prevention of prenatal alcohol exposure and intervention to mitigate alcohol’s postnatal effects, the Centers for Disease Control and Prevention (CDC) provides continuing education to healthcare providers through their FASD Regional Training Centers (RTCs). An online survey evaluated healthcare providers’ perceived competency after training. Cover letters with the survey link were electronically mailed to healthcare providers, who received training between 2002 and 2009 from the Midwest and Southeast RTCs. Eighty-two providers who treated women or children responded to the survey (7.5% response rate). Approximately 86% of providers who treated women have identified women ‘at risk’ for alcohol abuse with 90% indicating they would refer to Substance Abuse or Mental Health Services. However, over 25% perceived lack of training and limited time as barriers in treating women of childbearing age for at-risk drinking. Over 90% of providers who treated children reported feeling competent in recognizing FAS and other alcohol-related effects. Yet, only 23% of providers for children reported using FASD diagnostic schema and were more apt to use growth charts (70%) rather than lip philtrum guides (58%) or palpebral fissure length measurements (50%), tools typically used in FAS determination. These results suggest a need for training to focus on methodology that assists providers to easily incorporate screening, diagnostic, and treatment procedures into their daily practice